Womens Board Seeking Behaviour: A Conceptual Typology - Marinelli, Mellisa; Lord, Linley; Jefferson, Therese (ANZAM, 2012)
There is continued concern in Australia over the low representation of women on corporate boards. A range of strategies have been proposed to address a perceived need to provide training for ‘board ready’ women. One program is the provision of scholarships to complete a recognised company director’s program. Underlying this approach is an implied assumption that undertaking a company director’s course will lead to board appointments. This paper presents findings from interviews with six of ten women who won scholarships to undertake the course. Contrary to expectations, completion of the course did not lead to board seeking behaviour for most study participants. A conceptual typology to describe the board seeking behaviours has been developed.